Long-Term Cognitive Impairments of Sports Concussions in College-Aged Athletes: A Meta-Analysis. Issue 2 (24th February 2022) - Redlinger, Fanny; Sicard, Veronik; Caron, Gabriel; Ellemberg, Dave
ABSTRACT: Introduction/Purpose: This meta-analysis aimed to investigate the long-term (3+ months) consequences of concussion across cognitive domains (processing speed, memory, attention, and executive functions) and subdomains in young adult athletes (university, professional, or recreational). Methods: Six databases (EMBASE, PubMed, PsycINFO, SPORTDiscus, Web of Science, and Cochrane List of Registered Trials) were searched for studies that compared cognitive performance between athletes with a history of concussion (HOC) and control athletes who never sustained a brain injury. Thus, the analyses were restricted to the studies investigating sports concussions. Results: Nineteen studies, including 20 independent experiments with 1514 participants (521 HOC athletes, 1184 controls), were identified. Athletes from the HOC group sustained an average of 2.40 ± 0.99 concussions, with an average of 29.88 ± 19.26 months after injury. Importantly, all HOC athletes were tested at least 3 months after their most recent concussion. The results indicated significant medium-to-large group differences (Hedges' g = 0.55–1.03; P values < 0.0001) for executive functions subdomains on both standardized clinical tests and screening tools. Specifically, HOC athletes had lower cognitive performance relative to controls in strategy generation/regulation, verbal set-shifting and interference management on standardized clinical tests (Regensburger verbal fluency S words and G/R words), and response inhibition (ImPACT Impulse Control composite) and prospective working memory (Cogstate two-back task) on screening tools. Encoding phase of visual memory (Brief Visuospatial Memory Test) on standardized clinical tests approached significance (Hedges' g = 0.40; P values = 0.08). Conclusions: The current findings provide a preliminary guideline to clinicians for the assessment of cognition in HOC athletes and inform future guidelines on common data elements of sport-related concussions.